Application of automatic image analysis for quantitative morphological studies of peroxisomes in rat liver in conjunction with cytochemical staining with 3-3′-diaminobenzidine and immunocytochemistry - Beier, Konstantin; Fahimi, H. Dariush (Microscopy research and technique, 1992)
We describe the application of automatic image analysis for quantitative morphological studies of peroxisomes in rat liver. For automatic detection by light and electron microscopy peroxisomes must be stained with the alkaline DAB procedure for catalase. There is a good agreement between the results obtained by conventional morphometric techniques and by automatic image analysis of DAB-stained electron microscopic preparations. Moreover, the image analyzer may be used in conjunction with a light microscope for evaluation of semithin sections (1-0.25 μm), provided the section thickness factor is taken into consideration. This latter approach has proven highly efficient in estimation of peroxisome proliferation. The limitations of this method and the relevance of volume density as a reliable morphometric parameter for evaluation of peroxisome proliferation are discussed. In the second part of this study we present the application of image analysis for quantitation of alterations of individual peroxisomal enzyme proteins after treatment with bezafibrate in immunogold stained ultrathin sections. There is good agreement between the results of quantitative immunocytochemistry and Western (immuno) blot analysis of highly purified peroxisomal fractions. In our experience quantitative immunoelectron microscopy provides a versatile, highly sensitive, and efficient method for detection of modulations of various proteins in peroxisomes. Finally the limitations and prospects of quantitative immunocytochemistry for investigation of peroxisomal proteins are discussed. © 1992 Wiley-Liss, Inc.
Elektronische Reproduktion der Druck-Ausgabe 4. Februar 2005
Gesehen am 15.01.2025